Oxidative Stress and Antioxidant Defense in Endometriosis and Its Malignant Transformation - Iwabuchi, Takuya (Oxid Med Cell Longev, 2015)
The aim of this study was to investigate the role of redox status in endometriosis and its malignant transformation. A search was conducted between 1990 and 2014 through the English language literature (online MEDLINE PubMed database) using the keywords endometriosis combined with malignant transformation, oxidative stress, and antioxidant defense. In benign endometriosis, autoxidation and Fenton reaction of hemoglobin from the ferrous Fe(2+) (oxyhemoglobin) state to the ferric Fe(3+) (methemoglobin) state lead to production of excess reactive oxygen species (ROS) such as O(2) (−) and (∙)OH. Hemoglobin, heme, and iron derivatives in endometriotic cysts cause distortion in the homeostatic redox balance. Excess oxidative stress could trigger DNA damage and cell death. In contrast, endometriosis-associated ovarian cancer (EAOC) might be associated with an effective antioxidant defense, including heme oxygenases, cytochrome P450 family, and glutathione transferase family. The pattern of redox balance supports that enhanced antioxidants may be involved in the pathogenesis of malignant transformation. In conclusion, oxidant/antioxidant balance function is a double-edged sword, promoting cell death or carcinogenesis. Upregulation of antioxidant functions in endometriotic cyst may result in restoration of cell survival and subsequent malignant transformation.